2019
DOI: 10.3390/cancers12010021
|View full text |Cite
|
Sign up to set email alerts
|

Chaperoning STAT3/5 by Heat Shock Proteins: Interest of Their Targeting in Cancer Therapy

Abstract: While cells from multicellular organisms are dependent upon exogenous signals for their survival, growth, and proliferation, commitment to a specific cell fate requires the correct folding and maturation of proteins, as well as the degradation of misfolded or aggregated proteins within the cell. This general control of protein quality involves the expression and the activity of molecular chaperones such as heat shock proteins (HSPs). HSPs, through their interaction with the STAT3/STAT5 transcription factor pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 196 publications
0
20
0
Order By: Relevance
“…In term of HSP70, encoded by HSPA1B, has emerged as a promising antitumor target in various cancer. Recently, it is also revealed that HSP70 may serve as a diverse immunoregulatory factors by acting as a cytokine in antigen presentation, DC maturation, the activities of NK cells, and myeloid-derived suppressor cells (Jego et al, 2019). Correspondingly, it was illustrated that upregulation of HSPA1B was associated with poor outcomes in hepatocellular carcinoma (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In term of HSP70, encoded by HSPA1B, has emerged as a promising antitumor target in various cancer. Recently, it is also revealed that HSP70 may serve as a diverse immunoregulatory factors by acting as a cytokine in antigen presentation, DC maturation, the activities of NK cells, and myeloid-derived suppressor cells (Jego et al, 2019). Correspondingly, it was illustrated that upregulation of HSPA1B was associated with poor outcomes in hepatocellular carcinoma (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, increased abundance of M1-type macrophages, and CD8 + T cells were associated with favorable survival outcomes. As mentioned above, the six risk genes can not only have intrinsic roles in tumor growth and apoptosis (i.e., Guo and Dixon, 2016;Chen et al, 2019;Jego et al, 2019), but also serve as the immune-regulatory factors via antigen-presenting cells (APCs) and effector T lymphocytes (Borrego et al, 2006;Surmann et al, 2015;Ling et al, 2017;Zhu et al, 2018;Chen et al, 2019;Wu et al, 2019). Hence, it is worthwhile to explore the relationship between the risk groups and infiltrative immune cells in primary LGG.…”
Section: Discussionmentioning
confidence: 99%
“…Different animal species can also provide additional mechanistic insights into STAT evolution and the signaling cascades [38]. For instance, understanding STAT activation in the context of heat shock proteins (HSPs) is critical for their involvement in cellular stress and the immune response which was explored by Jego et al [39].…”
Section: Chapter 3: General Targeting Aspects To Block the Jak1/2/3/tmentioning
confidence: 99%
“…The strong relationship between the JAK/STAT signaling pathway and HSPs was recently reviewed by Jego et al [ 33 ]. The authors showed that most HSPs can be regulated by STAT proteins both in stress and non stress situations such as heat shock response [ 34 ], adaptation to reactive oxygen species [ 35 ], cell growth, and in response to many other stimuli [ 36 , 37 ].…”
Section: Heat Shock Protein Chaperonesmentioning
confidence: 99%
“…The authors showed that most HSPs can be regulated by STAT proteins both in stress and non stress situations such as heat shock response [ 34 ], adaptation to reactive oxygen species [ 35 ], cell growth, and in response to many other stimuli [ 36 , 37 ]. Conversely, HSPs control STAT3/STAT5 activation in cancer [ 33 ]. Based on these observations, it has become obvious that HSPs are of potential interest in MPN.…”
Section: Heat Shock Protein Chaperonesmentioning
confidence: 99%